2017
DOI: 10.3839/jabc.2017.023
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal activity of coriander and cinnamon oils prepared by various methods against three species of agricultural pests (Myzus persicae, Teyranychus urticae and Plutella xylostella)

Abstract: Agricultural pests, diamondback moth (Plutella xylostella), green peach aphid (Myzus persicae) and two-spotted spider mite (Teyranychus urticae), are becoming major pests in human dwellings in a variety of ways across the world. For management of these pests, the essential oils of Coriandrum sativum and Cinnamomum cassia prepared by steam distillation, hexane extraction and supercritical extraction methods were evaluated for the insecticidal effects. Using the contact bioassay, the LD 50 value of C. sativum oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
3
0
3
Order By: Relevance
“…Interestingly, Lo et al [26] reported that pyrethrum mixed with mineral oil was highly effective by reducing M. persicae population by over 75% in field conditions. Also, the insecticidal activity of Cinnamomum cassia and Coriandrum sativum oils showed that they could be an effective natural acaricide and insecticide [27]. For T. urticae, lethal toxicity of biopesticides (pyrethrins, azadirachtin, rotenone, and B. bassiana) was evaluated with T. urticae females and eggs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Lo et al [26] reported that pyrethrum mixed with mineral oil was highly effective by reducing M. persicae population by over 75% in field conditions. Also, the insecticidal activity of Cinnamomum cassia and Coriandrum sativum oils showed that they could be an effective natural acaricide and insecticide [27]. For T. urticae, lethal toxicity of biopesticides (pyrethrins, azadirachtin, rotenone, and B. bassiana) was evaluated with T. urticae females and eggs.…”
Section: Discussionmentioning
confidence: 99%
“…Using the contact bioassay, the LD 50 values of C. cassia oils prepared by steam distillation and hexane extraction methods were 5.96 and 4.64 µg/cm 2 , respectively, against T. urticae adults, and the LD 50 value of the essential oil by the supercritical extraction method was 6.50 µg/cm 2 against M. persicae adults. Finally, the research indicated that C. cassia oils are a promising natural acaricide and insecticide against pests [61].…”
Section: Insecticidal Activitymentioning
confidence: 98%
“…이 계피 정유 의 항균작용으로는 균 세포안의 전해질의 누설현상 유도 및 대 사작용의 저하로서 확인되었으며 [5], 이러한 항균작용과 더불어 옥수수바구미(Sitophilus zeamais)에 대한 살충 및 기피작용을 나 타내었다 [6]. 살충효과는 농업해충에서도 발견되었으며 실험에 사용된 농업해충으로는 복숭아혹진딧물(Myzus persicae), 배추좀 나방(Plutella xylostella), 및 점박이 응애(Tetranychus urticae) 등이었다 [7]. 이러한 살충효과를 보고한 논문은 특이하게도 정 유를 세가지 다른 방법을 이용하여 추출하였으며 이는 수증기 증류법, 용매추출법(solvent extraction), 및 초임계추출법 (supercritical extraction) 등이었다 [7].…”
Section: 서 론unclassified
“…살충효과는 농업해충에서도 발견되었으며 실험에 사용된 농업해충으로는 복숭아혹진딧물(Myzus persicae), 배추좀 나방(Plutella xylostella), 및 점박이 응애(Tetranychus urticae) 등이었다 [7]. 이러한 살충효과를 보고한 논문은 특이하게도 정 유를 세가지 다른 방법을 이용하여 추출하였으며 이는 수증기 증류법, 용매추출법(solvent extraction), 및 초임계추출법 (supercritical extraction) 등이었다 [7]. 수증기증류법 및 헥산을 이용한 용매추출법으로 추출한 계피정유는 각각 복숭아혹진딧 물에 대해서 5.96 및 4.64 µg/cm 2 의 살충효과를 나타내었다 [7].…”
Section: 서 론unclassified
See 1 more Smart Citation